PENGARUH PAJAK BUMI DAN BANGUNAN TERHADAP PENDAPATAN ASLI DAERAH DI KABUPATEN NIAS SELATAN - Suartini Manao (Universitas Nias Raya, 2022)
The research aims to determine the effect of land and building tax and how much influence it has on local revenue in South Nias Regency with the problem of not being optimal in collecting land and building tax and the utilization of local sources of income. The research method used is quantitative using secondary data from BPKPAD in the form of a report on the realization of the 2014-2021 land and building tax budget and regional original revenue for South Nias Regency. Data analysis used simple linear regression with 2 (two) assistance applications, namely Eviews 12 SV and IBM SPSS Statistics Version 25. Based on research data that PBB has a positive effect on regional income with a regression value of 0.567, which can be interpreted if land and building taxes have increased by 1 % then local revenue will increase by 56.7%. The magnitude of the influence of land and building taxes on local revenue is only 2.3%. Suggestions from researchers are 1) to collect and re-collect land and building NJOP data and 2) increase awareness of taxpayers and tax collection officers through intensive and sustainable outreach.